Kualitas Pelayanan Kesehatan Esensial pada Masa Pandemi Covid-19 Menggunakan Metode Servqual - Lestari, Jihan Mega; Indrawati, Fitri (Indonesian Journal of Public Health and Nutrition, 2023)
Background: During COVID-19 pandemic, health system required to continue providing maximum health services. This study aims to determine the quality of essential health services during the COVID-19 pandemic. Dimensions of the quality of health services studied refer to SERVQUAL (Service Quality) model of Parasuraman et al. (1988). Methods: Type of research used is quantitative research with a descriptive approach. The population 2844 patients with a total sample of 96 respondents. The data collection method used a questionnaire with a purposive sampling technique using non-probability sampling method. Results: results of Chi-Square test showed that service quality variables related to patient satisfaction on each servqual dimension were tangibles (p=0.034), reliability (p=0.001), responsiveness (p=0.003), assurance (p=0.014), and empathy (p=0.000). While in the calculation of the difference in the gap dimension of tangibles (gap score -0.49), reliability (gap score -0.056), responsiveness (gap score -0.26), assurance (gap score 0.195), and empathy (gap score 0.134). Conclusion: Essential health services at Puskesmas Rembang 1 are generally said to be unsatisfactory and there is a relationship on all dimensions of servqual with the quality of essential health services during the COVID-19 pandemic at Puskesmas Rembang 1 on the level of patient satisfaction.